Mediating effect of social support on the association between life events and depression: A cross-sectional study of adolescents in Chongqing China. Issue 51 (18th December 2020) - Liu, Liang; Liu, Chaojie; Ke, Xiong; Li, Ningxiu
Abstract : Abstract: Depression is one of the most common mental health problems in adolescents. The link between negative life events and depression has been well established. However, our understanding about the role of social support in the link, which is likely culture-dependent, is quite limited. This study aimed to determine the mediating effect of social support on the association between life events and depression in adolescents in Chongqing China. A total of 1512 adolescents aged 12 to 17 years old in Chongqing of China were selected using a stratified cluster sampling strategy. Depression symptoms, negative life events, and perceived social support of the participants were measured using the Children's Depression Inventory, Adolescent Life Event Scale, and Child and Adolescent Social Support Scale, respectively. Pearson correlation analyses were performed to detect their associations. A multivariate linear regression model was established to determine the association between life events and depression after adjustment for variations in socio-demographic variables. The mediating effect of social support on the association between negative life events and depression was tested using the structural equation model. About 16.8% of the participants were detected with depression. Depression was associated with negative life events and low levels of social support ( P  < .05). Both frequency and perceived importance of social support showed a mediating effect on the association between life events and depression. Social support has a mediating effect on the association between life events and depression. Strengthening social support may be considered as an effective interventional strategy on depression in adolescents.